Computational Spectroscopy of Ionic Liquids for Bulk Structure Elucidation. Issue 10 (29th July 2018) - Saielli, Giacomo
Abstract: "Computational spectroscopy" refers to quantum chemistry protocols capable of predicting the electronic and/or magnetic spectra of molecules. The most common techniques used for structural assignment are infrared, electronic, and NMR spectroscopies. Chemists can normally deduce the chemical structure of an unknown substance by using a vast collection of empirical relationships linking the spectral features with the presence or absence of functional groups and, this part mostly by NMR, the connectivity between them and the relative stereochemistry. Computational spectroscopy is a powerful aid for structural elucidation when empirical relationships do not suffice to unambiguously assign the structure. In these cases, the calculated spectrum of a putative structure is compared with the experimental one and the match, or lack thereof, between the two, measured by several statistical parameters, indicates whether or not that structure is the correct one. Is it possible to extend such protocols to bulk phases of complex fluids, such as ionic liquids, rather than covalent molecules, in order to get insights into the average structure of the fluid? It is the aim of this Progress Report to highlight recent advances in this field through the discussion of specific case studies. Abstract : Predicting NMR, vibrational, and electronic spectra of ionic liquids by means of state‐of‐the‐art quantum‐based computational protocols provides a way to validate the average structure of the fluid obtained by MD simulations or experiments, akin to structure validation methods used in organic chemistry.